(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Central Asia, with its strategic location, abundant natural resources, and expanding consumer base, holds significant potential for e-commerce growth. As an essential driver of economic development and job creation, e-commerce can transform the region’s trade landscape. However, its success hinges on the effective logistics infrastructure, which remains a critical challenge. This paper analyzes the logistics challenges facing Central Asia’s e-commerce sector and explores possible solutions that could bring sustained growth in Central Asians’ digital economy.